Ghost stories from the Pacific Northwest - MacDonald, Margaret Read, 1940- (American folklore series., 1995)
Contains first-person accounts of ghostly encounters in Oregon, Washington, and British Columbia, where the apparitions seem to be more or less non-threatening, and many are possessed with musical abilities.